PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN PADA SHOPPING CENTER BATU WONDERLAND KOTA BATU - Ni’matul Khoirunnisa; N. Rachma; Afi Rahmat Slamet (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACTThis study aims to determine whether the Marketing Mix consisting ofProduct, Price, Place and Promotion, influence the purchasing decision at Batuwonderland Shopping Center as well as analyze the most dominant factors thatinfluence it.The research method used is quantitative method with interview data collectiontechnique and questionnaire. The population in this study were the visitors andwho had visited the wonderland stone shopping center and samples taken as muchas 97 respondents using Non-Probability Sampling technique is the technique ofdetermining the sample based on certain considerations (purposive sampling).After the distribution of questionnaires, the results of the questionnaire wereanalyzed by using multiple linear regression analysis of path analysis (spss),determination coefficient and hypothesis test.The result of the research shows that marketing mix consisting of product, price,place, and promotion have positive and significant effect to purchasing decisionat wonderland stone shopping center and promotion variable has the mostdominant influence on purchasing decision at Batu wonderland shopping center.The conclusion of this research is that the better the marketing mix strategyapplied, the purchasing decision will increase.Keywords : product, price, place, promotion, buying dicision